HUBUNGAN INFORMASI IKLAN KOSMETIKA DENGAN SIKAP MAHASISWI MEMBELI PRODUK KOSMETIKA PADA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Susilawati, Susilawati; Rostamailis, Rostamailis; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this study is to see the relationship whether there is information of cosmetic’s advertisements with the attitude of student of 2014 entry year buying the lightening facial cosmetic products of Faculty of Tourism and Hospitality of State University of Padang. This study is quantitativedescriptive correlation. The population in this study is the entire students of Faculty of Tourism and Hospitality of 2014 entry year of the total 243 students and total of the samples are 71 students. The technique of getting the data is using questionnaires with the likert’s scale which has been tested for validity and reliability. The analysis of data is descriptive; analysis is conducted by normalitytest, linear-test, and hypothesis-test with moment product correlation. The result of the study shows that there is a significant relationship with the direction of negative correlation between the information of advertisements and the attitude of students who buy it. The result shows that the information of cosmetic’s advertisements stand on 82% with the high category and attitude of students in buying the lightening facial cosmetics stand in on 60% with low attitude category. Key words: information of advertisement, the attitude in buying the lightening facial cosmetics